PENGARUH PROSEDUR PEMBERIAN KREDIT TERHADAP PENINGKATAN JUMLAH NASABAH PADA BANK BRI CABANG MARISA KABUPATEN POHUWATO - Anas, Muhammad (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2018)
Basically, credit is something mostly needed by the society that can supporting and running well the commerce activities, whether in goods productions, service and also improving or fulfilling the need of society consumption. The aim of this research  is to analysis the provide credit facility, such as character, capacity, Capital, and the condition of economy towards some of bank customers of BRI Branch at Marisa in Pohuwato restrict. In this research  it is used questionnaire that distributing towards 40 respondents in order to get information about the problems which being related to the variables observed.  The analysis instrument used is multiple regressions. The result of this research showed that the research variable whether in a partial or simultaneous regression proved  having positive influence and significantly  towards improvement of BRI bank customers  in Marisa at Pohuwato District.